Genomics, proteomics and bioinformatics: all in the same boat - Russell, Robert B (BioMed Central, 2002)
A report on the Genomics, Proteomics and Bioinformatics for Medicine (GPBM) 2002 meeting, St. Petersburg to Moscow, Russia, 22-30 June 2002.